Observation of nonradiative energy transfer in the excitation of Nd3+ in GaP - DONEGAN, JOHN FRANCIS (American Physical Society, 1990)
We have carried out luminescence-excitation measurements on a Nd3+ complex in GaP in the range 1.5?2.2 eV to determine the mechanisms by which the internal Nd3+ luminescence is generated. At low temperatures we observe transitions into the 4S3/2 and 4F7/2 excited states of Nd3+ and two broad excitation bands whose integrated intensities are orders of magnitude greater than that of the Nd3+ excited states. These broadbands demonstrate for the first time that nonradiative energy transfer from external states is the dominant low-temperature mechanism for the excitation of Nd3+ luminescence in GaP. Reasonable assignments have been made for the origin of the broadbands on the basis of similar work carried out on rare-earth-doped II-VI semiconductors.
PUBLISHED
Keywords: Physics